Repeated training of accredited social health activists (ASHAs) for improved detection of visceral leishmaniasis cases in Bihar, India - Das, Vidya Nand Ravi (Pathog Glob Health, 2016)
Accredited Social Health Activists (ASHAs) are incentive-based, female health workers responsible for a village of 1000 population and living in the same community and render valuable services towards maternal and child health care, polio elimination program and other health care-related activities including visceral leishmaniasis (VL). One of the major health concerns is that cases remain in the endemic villages for weeks without treatment causing increased likelihood to treatment failure and disease transmission in the community. To address this problem, we have begun a training program for ASHAs to enhance early detection of potential VL cases and referring them to their local Primary Health Centers (PHCs) for diagnosis and treatment. The result of this training showed increased referral rate to PHCs for diagnosis and treatment. Encouraged with the results from a single training session, we determined in the present study whether repeated training of ASHAs resulted in an a further increase in VL case referral to the local PHCs. After two training sessions, VL referrals by ASHAs increased to 46% as compared to 28% after a single training session in this cohort and a baseline of 7% before training. ASHA training is an effective way to conduct active case detection of VL cases and should be repeated once a year.